A Wireless Sensor Network for Precise Volatile Organic Compound Monitoring - Gianfranco Manes; Giovanni Collodi; Rosanna Fusco; Leonardo Gelpi; Antonio Manes (International Journal of Distributed Sensor Networks)
A variety of methods have been developed to monitor VOC concentration in hazardous sites. The methods range from calculation to measurement, point measuring to remote sensing. Some are suited for leak detection, others for estimation of the annual emission or both. None of the following available methods comes close to the ideal method. A distributed instrument providing precise monitoring of Volatile Organic Compound (VOC) concentration in a petrochemical plant is described; it consists of a Wireless Sensor Network (WSN) platform whose nodes are equipped with meteorological/climatic sensors and VOC detectors. Internet connectivity is provided in real time at a one-minute sampling rate, thus providing environmental authorities and plant management with an unprecedented tool for immediate warning in case of critical events. The paper describes the WSN platform, detailing various units (gateways, nodes, detectors) and shows the features of scalability and reconfigurability, with minimal intrusiveness or obtrusiveness. Environmental and process data are forwarded to a remote server and made available to the authenticated users through a rich user interface that provides data rendering in various formats and worldwide access to data. A survey of the VOC detector technologies involved is also provided.